2016
DOI: 10.1007/s13277-015-4640-3
|View full text |Cite
|
Sign up to set email alerts
|

Number of negative lymph nodes as a prognostic factor for ypN0-N1 breast cancer patients undergoing neoadjuvant chemotherapy

Abstract: Some of node-positive patients could have a pathologically complete response in terms of lymph nodes. For these patients, the number of negative lymph nodes (NLNs) may be higher than that in the same-stage patients who initially received mastectomy. After neoadjuvant chemotherapy (NAC), the following treatment especially the postmastectomy radiotherapy (PMRT) is controversial for ypN1 (with one to three positive lymph nodes after NAC) patients. A total of 289 patients who received NAC from 2006 to 2009 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…[ 14 , 15 ] However, these studies are limited and controversial. Xin et al [ 16 ] found that less number of NLNs would benefit from PMRT in patients of ypN1 stage. Inconsistent with the study, Wu et al [ 7 ] found that patients with an elevated number of NLNs had better survival after PMRT.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 , 15 ] However, these studies are limited and controversial. Xin et al [ 16 ] found that less number of NLNs would benefit from PMRT in patients of ypN1 stage. Inconsistent with the study, Wu et al [ 7 ] found that patients with an elevated number of NLNs had better survival after PMRT.…”
Section: Discussionmentioning
confidence: 99%
“…Authors concluded that PMRT improved overall survival only in patients with initial T3 disease. Xin et al investigated the prognostic significance of number of negative lymph nodes (NLN) removed after NACT in a retrospective study [95]. The authors found that, PMRT improved OS (p < 0.05) and DFS (p < 0.05) in the subgroup of patients with ypN1 stage, and ≤13 NLN, however no benefit of PMRT was detected in patients with >13 NLN even they were ypN1 after NAC.…”
Section: Indications For Pmrt In Neoadjuvant Approachmentioning
confidence: 99%